2015
DOI: 10.4171/zaa/1530
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Control in Matrix-Valued Coefficients for Nonlinear Monotone Problems: Optimality Conditions I

Abstract: In this article we study an optimal control problem for a nonlinear monotone Dirichlet problem where the controls are taken as matrix-valued coefficients in L ∞ (Ω; R N ×N). For the exemplary case of a tracking cost functional, we derive first order optimality conditions. This is the first part out of two articles. This first part is concerned with the general case of matrix-valued coefficients under some hypothesis, while the second part focuses on the special class of diagonal matrices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In this case (see [12] and [13] ) the first-order optimality conditions can be represented as follows…”
Section: Thierry Horsin and Peter I Kogutmentioning
confidence: 99%
“…In this case (see [12] and [13] ) the first-order optimality conditions can be represented as follows…”
Section: Thierry Horsin and Peter I Kogutmentioning
confidence: 99%
“…In [2] we have derived first-order optimality conditions for optimal control problem (1)-( 4) and carried out their realization under some additional assumptions. We introduced the notion of a quasi-adjoint state ψ ε to an optimal solution y 0 ∈ W 1,p 0 (Ω) that was proposed for linear problems by Serovajskiy [5]) and showed that an optimality system can be recovered in an explicit form if the mapping U ad U → ψ ε (U) possesses the so-called H-property with respect to the pair of spaces L ∞ (Ω; R N ×N ), W 1,p 0 (Ω) .…”
Section: Minimizementioning
confidence: 99%
“…As a result, we show that each of the variational problems for the corresponding quasi-adjoint states has a unique solution, and these solutions form a weakly convergent sequence ψ ε θ ,θ ∈ H p U 0 , y θ (Ω) θ→0 in the variable space. This property suffices in order to establish that the optimality system for the problem (1)-( 4), that was derived in [2], remains valid even if H-property does not hold for the quasi-adjoint states.…”
Section: Minimizementioning
confidence: 99%
See 2 more Smart Citations